Variation in minerals, phenolics and antioxidant activity of peel and pulp of different varieties of peach (Prunus persica L.) fruit from Pakistan - Manzoor, Maleeha; Anwar, Farooq; Mahmood, Zahed; Rashid, Umer; Ashraf, Muhammad (MDPI, 2012)
Peach (Prunus persica L.), being a potential source of bioactive compounds, has been demonstrated to have medicinal benefits. In this study variation of minerals and antioxidant characteristics (total phenolic contents, total flavonoid contents, reducing power, inhibition of peroxidation using linoleic acid system and DPPH free radical scavenging activity) between peel and pulp parts of different peach varieties, namely Golden, Shireen, and Shahpasand were investigated. The peel and pulp extracts, derived from the varieties analyzed, exhibited an appreciable amount of total phenolics (TP) and total flavonoids (TF), ranging from 1,209.3–1,354.5, 711.7–881.3 mg GAE/100 g and 599.7–785.5, 301.3–499.7 mg CE/100 g on a dry weight basis, respectively. Reducing power of peel and pulp extracts (12.5 mg/mL concentration) ranged from 2.57–2.77 and 1.54–1.99.The inhibition of linoleic acid peroxidation and DPPH scavenging activity of the extracts varied from 70.8–80.9% and 66.8–76.5% in peels, and 51.9–60.1% and 43.4–49.1% in pulps. The mineral analysis revealed that the content of K was highest in both parts of the peach fruit followed by Mg, Ca, Fe, Mn and Zn. The results of our present study indicate that peach peel had significantly higher levels of minerals, antioxidant capacity and phenolics than those of the pulp, suggesting the intake of unpeeled peach as a potential source of high-value components. The peach peel can be a useful as a viable source of natural antioxidants for functional foods and nutraceutical applications.